Longitudinal Relations Between Internet Gaming Disorder Symptoms, Depressive Symptoms, and Hikikomori Symptoms Among Young Gamers – Random Intercept Cross-Lagged Panel Model With Contextual Factors. - Ye, Xingcan; Fong, Ted C. T.; Yip, Paul S. F. (Journal of Youth & Adolescence, 2026)
Despite the high comorbidity of internet gaming disorder symptoms, depressive symptoms, and hikikomori symptoms (severe social withdrawal), their longitudinal relations remain underexplored, especially whether they directly exacerbate one another over time or stem from shared underlying vulnerabilities. The present study used random intercept cross-lagged panel models to differentiate longitudinal within-person effects from stable between-person associations between internet gaming disorder, depressive, and hikikomori symptoms. The sample comprised 1560 gamers (45.3% female, M = 23.38, SD = 3.81 years) in Hong Kong who played internet games for at least three hours per week. Participants were divided into two age groups: 875 youth (43.20% female, M = 20.52, SD = 2.38 years) and 685 adults (47.88% female, M = 27.03, SD = 1.42 years). Including family and in-game contextual factors at the between-person level, two random intercept cross-lagged panel models across age groups were constructed and revealed developmental differences. Among youth gamers, hikikomori symptoms positively predicted depressive symptoms, and internet gaming disorder symptoms marginally predicted higher hikikomori symptoms. No significant within-person effects were found in adult gamers. Internet gaming disorder, depressive, and hikikomori symptoms showed significant positive between-person associations, and the escapism motive was a common risk factor in both youth and adult gamers. Playing specific game genres was associated with comorbidity among youth gamers, whereas the disruptor trait was associated with comorbidity among adult gamers. Lower family satisfaction contributed to depressive and hikikomori symptoms. These results highlight that longitudinal within-person relations might explain the comorbidity among internet gaming disorder, depressive, and hikikomori symptoms in youth gamers, whereas stable between-person associations may account for their co-occurrence in adult gamers. Clinical interventions should be developed for the sequential symptom cascade in youth and target shared underlying vulnerabilities to reduce comorbidity in adult gamers.